Sand cat Rabies in Saudi Arabia: Leveraging to Improve Spillover Surveillance and One Health Impact. (March 2022) - Fagbo, S.; Asiri, A.
Abstract : Purpose: Exploit a sand cat ( Felis margarita ) associated rabies outbreak to strengthen One Health Approach and Enhance Pathogen spillover surveillance mechanisms in Saudi Arabia. Methods & Materials: Documentation on the outbreak response from the Ministries of Environment. Water and Agriculture (MEWA) and Health (MOH) were reviewed. With an experienced wildlife veterinarian from the Wildlife Authority added, the review team sought to understand the possible transmission pathways to the sand cat. Additonally, it sought to characterize the potential direct and indirect public health threats to man and animals Results: The rabies outbreak and spillover event were due to an unprovoked attack on a 55-year-old farmer on his farm by a sand cat in Sharri, a village in the Qaseem region of Saudi Arabia. The victim killed the cat prior to presenting for medical attention. The coordinated and rapid One Health response between MEWA and MOH led to the rapid diagnosis of rabies in the brain of the sand cat using Direct Fluorescent Antibody testing. The small size and solitary life style of the sand cat in its harsh, desert habitat in Central Saudi Arabia provoked theories of cross-species transmission from known primary reservoirs: bats or foxes. The prevailing passive nature of rabies surveillance and the lack of a robust laboratory surveillance mechanism precluded confirmation of these theories by viral characterization. We observed that ongoing uncontrolled illegal poaching and online sales of sand cat could serve as pathways for future rabies spillovers in man and other animals. Additionally, spillovers can potentially involve other pathogens primarily or secondarily harbored by sand cats. Conclusion: This first report of rabies in sand cats further highlights how the One Health approach in disease control and prevention and pathogen spillover monitoring. Furthermore, enhanced rabies spillover surveillance at the wildlife-domestic animal interface can be leveraged with to understand other possible pathogen spillovers in our desert ecosystem. The need for strengthening the domestic and wildlife surveillance mechanism, including having dedicate animal control officers, cannot be overemphasized.